PENGARUH KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP PROFESIONALISME GURU DENGAN KEPUASAN KERJA DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (Studi Kasus di MTs dan MA Miftahul Ulum Banyu Putih Kidul Jatiroto Lumajang) - Mohamad Wajihidin; M. Fathorrazi; Diana Sulianti K Tobing (STIE Mandala Jember, 2014)
The education has a very important role for the development of a country. The purposes of this research are to analyze and get a picture about the influence of compensation on organizational commitment, the influence of compensation on job satisfaction, organizational commitment influence on teacher professionalism, the influence of the compensation for their professionalism, the influence of organizational culture on organizational commitment, the influence of organizational culture on job satisfaction, customer satisfaction work on the professionalism of teachers, and the influence of the organizational culture on teacher professionalism. This research used Explanatory Research namely clarify the causal relationship between the independent variable and dependent variable. The research conducted in MTs and MA Miftahul Banyuputih Kidul Jatiroto Lumajang. Populations in this research are 115 teachers at MTs and MA Miftahul Ulum Banyuputih Kidul Jatiroto Lumajang. The sampling used a table developed by Isaac and Michael with 1 % error rate and the sum of samples in this research are 100 respondents. This study used primary data and secondary data obtained. The primary data is done by means of observation, interviews and questioner, and the secondary data have done by collecting documents on the Institute. The analysis in this research used the Structural Equation Model (SEM) that is technique statistic that allows testing of a relatively complex network of relationships simultaneously.The results of the analysis showed that the compensation effect significantly to job satisfaction, but compensation didn’t influence significantly on organizational commitment. Then organizational commitment significantly influence the professionalism of teachers, the compensation didn’t impact significantly on teacher professionalism. Organizational culture significantly influence the organizational commitment, organizational culture a significant effect on job satisfaction, job satisfaction was significantly influential on teacher professionalism, and organizational culture significantly influence the professionalism of teachers.